Dinner with the roommates: trophic niche differentiation and competition in a mutualistic ant‐ant association. (27th December 2020) - Sprenger, Philipp P.; Müsse, Christian; Hartke, Juliane; Feldmeyer, Barbara; Schmitt, Thomas; Gebauer, Gerhard; Menzel, Florian
Abstract : 1. The potential for competition is highest among species in close association. Despite net benefits for both parties, mutualisms can involve costs, including food competition. This might be true for the two neotropical ants Camponotus femoratus and Crematogaster levior, which share the same nest in a presumably mutualistic association (parabiosis). 2. While each nest involves one Crematogaster and one Camponotus partner, both taxa were recently found to comprise two cryptic species that show no partner preferences and seem ecologically similar. Since these cryptic species often occur in close sympatry, they might need to partition their niches to avoid competitive exclusion. 3. Here, we investigated first, is there interference competition between parabiotic Camponotus and Crematogaster, and do they prefer different food sources under competition? And second, is there trophic niche partitioning between the cryptic species of either genus? 4. Using cafeteria experiments, neutral lipid fatty acid and stable isotope analyses, we found evidence for interference competition, but also trophic niche partitioning between Camponotus and Crematogaster . Both preferred protein‐ and carbohydrate‐rich baits, but at protein‐rich baits Ca. femoratus displaced Cr. levior over time, suggesting a potential discovery‐dominance trade‐off between parabiotic partners. Only limited evidence was found for trophic differentiation between the cryptic species of each genus. 5. Although we cannot exclude differentiation in other niche dimensions, we argue that neutral dynamics might mediate the coexistence of cryptic species. This model system is highly suitable for further studies of the maintenance of species diversity and the role of mutualisms in promoting species coexistence. Abstract : The neotropical ants Camponotus femoratus and Crematogaster levior are mutualists and share nests. Both taxa comprise two cryptic species. This might cause competition between mutualistic partners and between sister species. We investigated the trophic niches of all cryptic species. Our data suggest niche partitioning and a dominance‐discovery trade‐off between Camponotus and Crematogaster, but only limited differentiation between sister species. While differentiation in other niche dimensions remains possible, neutral dynamics might mediate the coexistence of cryptic species.